2016
DOI: 10.1155/2016/5281267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the New Aldose Reductase Inhibitor Benzofuroxane Derivative BF-5m on High Glucose Induced Prolongation of Cardiac QT Interval and Increase of Coronary Perfusion Pressure

Abstract: This study investigated the effects of the new aldose reductase inhibitor benzofuroxane derivative 5(6)-(benzo[d]thiazol-2-ylmethoxy)benzofuroxane (BF-5m) on the prolongation of cardiac QT interval and increase of coronary perfusion pressure (CPP) in isolated, high glucose (33.3 mM D-glucose) perfused rat hearts. BF-5m was dissolved in the Krebs solution at a final concentration of 0.01 μM, 0.05 μM, and 0.1 μM. 33.3 mM D-glucose caused a prolongation of the QT interval and increase of CPP up to values of 190 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…We have previously shown that the selective ALR2 inhibitor 5(6)-(benzo[𝑑]thiazol-2-ylmethoxy) benzofuroxane (BF-5m), a novel nonhydantoin noncarboxylic acid benzofuroxane derivative [ 18 , 19 ], reduced QT interval in isolated rat heart perfused with Krebs solution containing high glucose concentrations [ 11 ]. In order to gain insights into the molecular targets of BF-5m we translated the previous above observation on cultured embryonic rat heart ventricle H9c2 cells under high glucose stimulus and show here that the ALR2 inhibitor BF-5m is able to increase cell viability, by reducing the cytotoxic effects induced by hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the selective ALR2 inhibitor 5(6)-(benzo[𝑑]thiazol-2-ylmethoxy) benzofuroxane (BF-5m), a novel nonhydantoin noncarboxylic acid benzofuroxane derivative [ 18 , 19 ], reduced QT interval in isolated rat heart perfused with Krebs solution containing high glucose concentrations [ 11 ]. In order to gain insights into the molecular targets of BF-5m we translated the previous above observation on cultured embryonic rat heart ventricle H9c2 cells under high glucose stimulus and show here that the ALR2 inhibitor BF-5m is able to increase cell viability, by reducing the cytotoxic effects induced by hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…On this base the initial inhibition of the endogenous ALR2 with a benzofuroxane derivative BF-5m [ 11 ] represented a new and important strategy to indirectly approach high glucose-induced QT interval prolongation. Insights acquired here show for the first time that the blockade of the ALR2 with BF-5m causes changes of the expression of H9c2 KCNQ1/KCNE1 potassium channels subunits at the plasma membrane level and not at the level of the mitochondria after high glucose exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the selective ALR2 inhibitor 5(6)-(benzo[ ]thiazol-2-ylmethoxy) www.oncotarget.com benzofuroxane (BF-5m), a novel nonhydantoin noncarboxylic acid benzofuroxane derivative [18,19], reduced QT interval in isolated rat heart perfused with Krebs solution containing high glucose concentrations [11]. In order to gain insights into the molecular targets of BF-5m we translated the previous above observation on cultured embryonic rat heart ventricle H9c2 cells under high glucose stimulus and show here that the ALR2 inhibitor BF-5m is able to increase cell viability, by reducing the cytotoxic effects induced by hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…On this base the initial inhibition of the endogenous ALR2 with a benzofuroxane derivative BF-5m [11] represented a new and important strategy to indirectly approach high glucose-induced QT interval prolongation. Insights acquired here show for the first time that the blockade of the ALR2 with BF-5m causes changes of the expression of H9c2 KCNQ1/KCNE1 potassium channels subunits at the plasma membrane level and not at the Merged images did not demonstrate a significant colocalization of KCNE1 with the mitochondria in H9c2 exposed to normal or high glucose medium and receiving DMSO 0.1 µM or BF-5m 0.01-0.025-0.05 µM pretreatment.…”
Section: Discussionmentioning
confidence: 99%